Work of Medical Sciences students in the confrontation with COVID-19 in Cienfuegos - Lya del Rosario Magariño Abreus; Rodolfo Javier Rivero Morey; Alejandro Pérez Capote; Evelyn Delgado Rodriguez; Carla María García San Juan; María Aurelia San Juan Bosh (Medisur)
Background: the impact tasks carried out by medical sciences students constituted an essential factor in the confrontation with COVID-19. Objective: to characterize the medical science students work in the confrontation with COVID-19 in Cienfuegos. Methods: observational, descriptive and cross-sectional study from February to September 2021. The universe consisted of 1815 Dentistry and Medicine students who were fighting against COVID-19. The whole universe was studied. Variables such as the municipality of origin, members of the Student Helpers Movement, impact task, place where they worked and multiple tasks were also analyzed. Descriptive statistical techniques were used. Results: the average age was 20.6 years and the female sex predominated (70%). The medical career was the most represented (96.0%). The Cienfuegos municipality had the highest student participation (49.4%). All students were incorporated into at least one impact task. 99.8% contributed to the active research in the community. The task with the greatest impact for first-year students was research (90%), while vaccination was in the remaining academic years. Conclusions: medical science students from Cienfuegos joined different impact tasks in the fight against COVID-19, which contribute to their comprehensive training and show the sense of duty that characterizes health personnel trained in the country.